Inequality, aging, and the middle-income trap - Chen Wang; Jiajun Lan (Asian Development Bank Institute (ADBI), 2017)
Based on required growth rate and actual growth rate, this paper proposes a method to construct measures to indicate the probability of a country escaping the middle income trap (MIT). A second contribution of this paper is to model this probability using 1960-2015 cross-country data, focusing on the roles of income distribution or inequality and aging. It is found that: (1) both the level of, and the change in, inequality are important drivers of MIT, with surprisingly large impacts; (2) relative to income distribution, aging is found to be much less important in terms of both magnitude and statistical significance; and (3) total factor productivity growth and structural transformation are fundamental drivers for an economy to escape the MIT. However, earlier industrialization may not generate the expected impact on growth, as the probability of escaping the MIT is found to display a U-pattern relationship with industrialization.
Keywords: D33; D63; O4; O14; 330; middle income trap; growth theory; income distribution; inequality; aging